2022
DOI: 10.48550/arxiv.2206.01191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EfficientFormer: Vision Transformers at MobileNet Speed

Abstract: Vision Transformers (ViT) have shown rapid progress in computer vision tasks, achieving promising results on various benchmarks. However, due to the massive number of parameters and model design, e.g., attention mechanism, ViT-based models are generally times slower than lightweight convolutional networks. Therefore, the deployment of ViT for real-time applications is particularly challenging, especially on resource-constrained hardware such as mobile devices. Recent efforts try to reduce the computation compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Hybrid Models. Recent works [7,17,23,29,35] have shown that combining convolution and Transformer as a hybrid architecture helps absorb the strengths of both architectures. BoTNet [29] replaces the spatial convolutions with global self-attention in the final three bottleneck blocks of ResNet.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Hybrid Models. Recent works [7,17,23,29,35] have shown that combining convolution and Transformer as a hybrid architecture helps absorb the strengths of both architectures. BoTNet [29] replaces the spatial convolutions with global self-attention in the final three bottleneck blocks of ResNet.…”
Section: Related Workmentioning
confidence: 99%
“…Mobile-Former [2] combines with the proposed lightweight cross attention to model the bridge, which is not only computationally efficient, but also has more representation power. EfficientFormer [17] complies with a dimension consistent design that smoothly leverages hardware-friendly 4D MetaBlocks and powerful 3D MHSA blocks. In this paper, we design a family of Next-ViT models that adapt more to the realistic industrial scenarios.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations